Intensitas Kerusakan Penyakit Darah Pisang di Kampung Bowi Subur SP VI Distrik Masni Kabupaten Manokwari - Nelson Paskal Weyai; Maria Justina Sadsoeitoeboen; Fajar Ria Dwi Natalia Sianipar; Simon Sutarno; Agatha Cecilia Maturbongs (Igya ser hanjop: Jurnal Pembangunan Berkelanjutan, 2022)
Farmers in Indonesia suffer losses due to banana blood disease. One of the districts that experienced a decline in banana production were the District of Masni, Manokwari Regency. Through this research, an analysis of banana varieties that were infected with banana blood disease was carried out in Bowi Subur Village of Masni District. A survey method was used in observing disease symptoms that appeared on banana plant organs, more over some interviews was done with farmers. The results showed as many as 7 varieties of bananas were attacked by the banana blood disease. The level of damage found in each banana variety is different. Banana varieties that show symptoms of disease with a level of damage of 70% are kapok bananas (Musa balbisiana), raja bananas (Musa paradisiaca), and muslin bananas (Musa acuminata), varieties with damage levels > 30-70%, namely tanduk bananas (Musa paradisiaca), susu banana (Musa acuminata), Ambon banana (Musa acuminata), varieties with <30% damage rate are lilin banana (Musa acuminata). Keywords: banana blood disease, banana varieties, Manokwari regency